Mastering SharePoint 2019. (Packt Publishing, 2019)
Leverage Microsoft SharePoint 2019 features and capabilities to maximum advantage About This Video Learn the core and advanced development features of SharePoint 2019 and its surrounding development frameworks for app development Explore and create webhooks and handle requests using them Learn to integrate Office products with SharePoint Effectively use and manage SharePoint search capabilities to enhance user experience In Detail SharePoint 2019 is designed to be compelling, flexible, mobile, and easier to use. This course will be a perfect guide to take your skills in Microsoft SharePoint to the next level. Learn to maximize your skills using lists and libraries, team sites, branding, and communication sites to give you an edge over other SharePoint developers. This course will develop and take your intermediate skills to the next level.You will learn to develop an application through Microsoft SharePoint and then cover all the new features that SharePoint 2019 has to offer. You will learn to set up and manage your SharePoint business site on the cloud with SharePoint Online. You will then learn collaboration with other Microsoft products and services. Lastly, some interesting tips, tricks, and developers' best practices will be revealed. By the end of the course, you will have mastered SharePoint 2019 and will be confident using this knowledge in your organization and to support your own career advancement. Audience This course is for web developers, architects, admins, business professionals, or anyone who uses or is familiar with the SharePoint platform and wants to take their skills to an advanced level. Those who simply want to validate their skills against the new features in SharePoint 2019 will also benefit from the course. Basic knowledge of SharePoint is assumed.